Do Corporate Taxes Reduce Productivity and Investment at the Firm Level? Cross-Country Evidence from the Amadeus Dataset - Schwellnus, Cyrille (OECD Publishing, 2008)
This paper uses a stratified sample of firms across OECD economies over the period 1996-2004 to analyse the effects of corporate taxes on productivity and investment. Applying a differences-in-differences estimation strategy which exploits differential effects of corporate taxes on firms with different profitability, it is found that corporate taxes have a negative effect on productivity at the firm level. The effect is negative across firms of different size and age classes except for the small and young, which may be attributable to the relatively low profitability of small and young firms. The negative effect of corporate taxes is particularly pronounced for firms that are catching up with the technological frontier. In the investment analysis, the results suggest that corporate taxes reduce investment through an increase in the user cost of capital. This may partly explain the negative productivity effects of corporate taxes if new capital goods embody technological change
Keywords: Economics